PENGARUH MODEL PEMBELAJARAN INKUIRI HIPOTETIK TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN KETERAMPILAN PROSES SAINS SISWA SMP - KUSMIANTI, KUSMIANTI (Universitas Mahasaraswati Mataram, 2019)
The purpose of this research is to analyze: (1) the difference of critical thinking skills (CTS) and science process skills(SPS) between student?s group who are managed with hypothetical inquiry model and conventional learning model, (2) the difference of critical thinking skills (CTS) between student?s group who are managed with hypothetical inquiry model and conventional learning model, (3) the difference of science process skills (SPS) between student?s group who are managed with hypothetical inquiry model and conventional learning model. This research is quasi experiments with post-test only control group design factorial 2x1. Data of critical think skill are collected by using test and data of science process skillscollected by using test and observation. Data analyzed by using descriptive analyze and one way MANOVA.It is found: (1) there is significant difference of critical thinking skills (CTS) and science process skills(SPS) between student?s group who are managed with hypothetical inquiry model and conventional learning model (F=59,161; p<0,05), (2) there is significant difference of critical thinking skills (CTS) between student?s group who are managed with hypothetical inquiry model and conventional learning model(F=22,219; p<0,05), (3) there is significant difference of science process skills (SPS) between student?s group who are managed with hypothetical inquiry model and conventional learning model (F=113.559; p<0,05).